2015
DOI: 10.1038/nm.3914
|View full text |Cite
|
Sign up to set email alerts
|

The oral and gut microbiomes are perturbed in rheumatoid arthritis and partly normalized after treatment

Abstract: We carried out metagenomic shotgun sequencing and a metagenome-wide association study (MGWAS) of fecal, dental and salivary samples from a cohort of individuals with rheumatoid arthritis (RA) and healthy controls. Concordance was observed between the gut and oral microbiomes, suggesting overlap in the abundance and function of species at different body sites. Dysbiosis was detected in the gut and oral microbiomes of RA patients, but it was partially resolved after RA treatment. Alterations in the gut, dental o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

71
1,241
13
26

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,360 publications
(1,351 citation statements)
references
References 47 publications
71
1,241
13
26
Order By: Relevance
“…Liu et al (36) Gut microbiome DMARD-naive patients with early RA had increased Lactobacillus abundance and diversity compared to healthy controls. Zhang et al (39) Gut microbiome Dysbiosis in the gut (and oral) microbiome of patients with RA was partially resolved after RA treatment; Lactobacillus salivarius was overrepresented in patients with RA, while Haemophilus strains were relatively depleted. Vaahtovuo et al (38) Bacterial diversity Widespread microbial differences found in intestinal microbiota of patients with early RA compared to patients with fibromyalgia.…”
Section: Gutmentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al (36) Gut microbiome DMARD-naive patients with early RA had increased Lactobacillus abundance and diversity compared to healthy controls. Zhang et al (39) Gut microbiome Dysbiosis in the gut (and oral) microbiome of patients with RA was partially resolved after RA treatment; Lactobacillus salivarius was overrepresented in patients with RA, while Haemophilus strains were relatively depleted. Vaahtovuo et al (38) Bacterial diversity Widespread microbial differences found in intestinal microbiota of patients with early RA compared to patients with fibromyalgia.…”
Section: Gutmentioning
confidence: 99%
“…Altering the local T cell balance in this way may lead to systemic autoimmunity. Indeed, several studies have demonstrated that gut dysbiosis occurs in RA (36)(37)(38)(39) and that specific bacteria, including Lactobacillus (36) and Prevotella copri (37), are more abundant in new, untreated RA patients.…”
Section: Gutmentioning
confidence: 99%
See 1 more Smart Citation
“…[52][53][54][55][56][57][58] Although most of them do not go beyond simple association tests, 2 approaches should be specifically mentioned as similarly to our method they attempt to pinpoint microbes that have potential causal effect on unrelated phenotype. 52,59 The first one, LEfSe, is a popular tool that has been already utilized by several groups.…”
Section: Microbiota Characterizationmentioning
confidence: 99%
“…Lactobacillus than that of the control group. In a recently published paper, compositional and functional alterations in RA-associated gut and oral microbiomes were observed, which were partly relieved by disease modifying anti-rheumatic drugs (DMARD) treatment [18]. To delineate the features of the RAassociated gut microbiome, the authors performed a microbiome genome-wide association study identifying 117,219 gene markers that were differentially enriched in RA patients and controls and clustered these genes into metagenomic linkage groups (MLGs) on the basis of their correlated abundance variation among samples.…”
Section: Gastrointestinal Microbiota In Rheumatoid Arthritis Patientsmentioning
confidence: 99%